A water-soluble fluorescent sensor for the quick discrimination of H2O and D2O by notable signal outputs and the real-time monitoring of food spoilage in a non-contact mode. (26th October 2021) - Zhang, Shengjun; Li, Zhao; Zhang, Bo; Dong, Fenghao; Han, Bingyang; Lv, Jiawei; Sun, Yuqing; Lu, Huiming; Yang, Yuan; Ma, Hengchang
Abstract : Due to the very similar chemical and physical properties, D2 O and H2 O cannot be discriminated easily by convenient and cost-effective ways. Abstract : Due to the very similar chemical and physical properties, D2 O and H2 O cannot be discriminated easily by convenient and cost-effective ways. Up to now, small organic molecules with active deprotonating ability in a very weak alkaline solution are proposed to deal with this fascinating yet challenging research. In this contribution, TPA-DP-COOH, a carboxylic acid group-substituted fluorescent substance, is demonstrated as a sensor to detect D2 O and H2 O with an external interference-free style, which not only displays a huge different signal output in D2 O and H2 O, but also very low limits of detection (LOD) as 49.08 ppm (D2 O in H2 O) and 0.23 ppm (H2 O in D2 O), respectively. Thus, these excellent sensing behaviors encourage us to fabricate TPA-DP-COOH and TPA-DP-COOK-absorbed filter papers as cost-effective and portable test strips, which are able to monitor the spoilage of Dimocarpus longan Lour and white leg shrimp in a non-contact mode during the storing process.